Efficacy, sustainability and safety of natural food preservatives: a study on muffins preserved with plant extracts - Pedrosa, Mariana C. (2020)
The natural preservatives do not show deep changes on the nutritional profile, and, pending their efficacy on antioxidant activity, should be encouraged as alternatives to synthetic preservatives. The natural additives should be encouraged to be used as alternatives to synthetic ones. They did not impact the colour of muffins.